Pulmonary alveolar proteinosis in a 10-year-old girl masquerading as tuberculosis - Baro, Abhamoni (Oxf Med Case Reports, 2015)
Pulmonary alveolar proteinosis (PAP) is a rare pulmonary disease. Diagnosis is established by bronchoalveolar lavage (BAL), which has macroscopic ‘milky appearance’, and in the presence of typical computed tomography, findings are diagnostic of PAP but, however, the feature of periodic acid–Schiff-positive eosinophilic proteinaceous fluid raises the confidence of the diagnosis. We report late-onset PAP in a 10-year-old girl who had acid fast bacilli on an initial BAL examination, but was subsequently diagnosed as PAP.